Performance Evaluation of Web Portals - Abdul Rahim, Rahela; Ibrahim, Haslinda; Syed Yahaya, Sharipah Soaad; Khalid, K. (IJMO, 2011)
Performance of Web portals at the system level has not been given much attention. The evaluation at the system level is importance for systems maintenance or further improvement. This study develops an evaluation model based on queuing theory at a system level of web portals performance for a university. A system level performance model views the system being modeled as a ‘black box’ which considers the arrival rate of packets to the portals server and service rate of the portals server. These two parameters are important elements to measure web portals performance metrics such as server utilization, average server throughput, average number of packet in the server and mean response time. This study refers to infinite population and finite queue. The proposed analytical model is simple in such a way that it is easy to define and fast to interpret the results but still represents the real situation. The results present the performance of six parallel web portals